Automatic sound detection and recognition for noisy environment - Dufaux, Alain; Besacier, Laurent; Ansorge, Michael; Pellandini, Fausto (My University, 2000)
This paper addresses the problem of automatic detection and recognition of impulsive sounds, such as glass breaks ,human screams, gunshots, explosions or door slams. A complete detection and recognition system is described and evaluated on a sound database containing more than 800 signals distributed among six different classes. Emphasis is set on robust techniques, allowing the use of this system in a noisy environment. The detection algorithm, based on a median filter, features a highly robust performance even under important background noise conditions. In the recognition stage, two statistical classifiers are compared, using Gaussian Mixture Models (GMM) and Hidden Markov Models (HMM), respectively. It can be shown that a rather good recognition rate (98% at 70dB and above 80% for 0dB signal-to-noise ratios) can be reached, even under severe gaussian white noise degradations.
Keywords: Impulsive sound detection; Soundrecognition; Gaussian Mixtures; Hidden MarkovModels; Multimodels; Robustness; Backgroundnoise; Telesurveillance; Tele-assistive technologies